2015
DOI: 10.4081/ripppo.2015.185
|View full text |Cite
|
Sign up to set email alerts
|

Psychoanalytic psychotherapy and the pregnant therapist: a literature review

Abstract: Researchers and clinicians seem to agree that the psychotherapist’s pregnancy is an unique moment of psychotherapy psychoanalytic process. In Brazil, 89% of psychologists belong to the female gender, being that the practice of psychotherapy, in its great majority, is performed by women. In spite of the relevance of the subject and of its impact on psychotherapies, there are few current studies, most of them dealing with adult patients. The objective of this study was to perform a systematic review of the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This study presents a first attempt to investigate the psychodynamic psychotherapeutic process of a schoolaged child and her therapist who becomes pregnant during treatment, based on the Q method. The literature has shown that the impact of pregnancy affects both therapist and patient, and that it can be a difficult and more insecure time for children during their treatment (Schmidt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study presents a first attempt to investigate the psychodynamic psychotherapeutic process of a schoolaged child and her therapist who becomes pregnant during treatment, based on the Q method. The literature has shown that the impact of pregnancy affects both therapist and patient, and that it can be a difficult and more insecure time for children during their treatment (Schmidt et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research on adult patients and children discusses the repercussions of the psychotherapist's pregnancy on treatment (Schmidt et al, 2015, Tonon et al, 2012, Wolfe, 2013. Some point in the direction that pregnancy catalyzes and facilitates various aspects of the process (Tonon et al, 2012;Wolfe, 2013), while others point out the difficulties that may occur in a treatment with the pregnant therapist.…”
Section: Psicoterapia Psicodinámica De Niños Y Embarazo De Terapeuta:mentioning
confidence: 99%
See 3 more Smart Citations